Adsorption removal of natural organic matters in waters using biochar. (July 2018) - Lee, Duu-Jong; Cheng, Ya-Ling; Wong, Ruei-Jyun; Wang, Xiao-Dong
Highlights: Use of a biochar to adsorb organic matters in waters is studied. Biochar can remove all organic matters of all molecular weights. Adsorption kinetics of organic matters of different molecular weights were discussed. Abstract: This work concerns the adsorption of aromatic organic matter from river water using various doses of a simulated biochar. The water yielded five UV254 peaks associated with organic matters in size exclusion chromatography (SEC), corresponding to molecular weights (MW) of 10, 000, 6500, 4800, 3000, and 1500 Da. Biochar removes all of these peaks with an overall adsorption of 6.4 mg-DOC/g-C, and preferentially removes organic matter with high MW. Physisorption control in a pseudo-second-order type model fits the adsorption kinetics. Biochar can therefore be used as an efficient adsorbent of organic matter in water.